Automatic control in aerospace : Aerospace Control '94 : a postprint volume from the IFAC symposium, Palo Alto, California, USA, 12-16 September 1994 - Schaechter, D. B.; Lorell, K. R. (IFAC Postprint Volume., 1995)
An important, successful area for control systems development is that of state-of-the-art aeronautical and space related technologies. Leading researchers and practitioners within this field have been given the opportunity to exchange ideas and discuss results at the IFAC symposia on automatic control in aerospace. The key research papers presented at the latest in the series have been put together in this publication to provide a detailed assessment of present and future developments of these control system technologies.